Neuropeptide Y in PTSD, MDD, and chronic stress: A systematic review and meta‐analysis. Issue 5 (11th February 2020) - Tural, Umit; Iosifescu, Dan V.
Abstract: Previous studies have suggested that neuropeptide Y (NPY) levels may be altered in patients with major depressive disorder (MDD), post‐traumatic stress disorder (PTSD) and chronic stress. We investigated, through systematic review and meta‐analysis, whether the mean levels of NPY are significantly different in patients with MDD, PTSD or chronic stress, compared to controls. The main outcome was the pooled standardized mean difference (SMD) with 95% confidence intervals between cases and controls, using the random‐effects model. Heterogeneity and publication bias were evaluated. Thirty‐five studies met eligibility criteria. Meta‐regression determined that medication and sex could explain 27% of the between‐study variance. Females and participants currently prescribed psychotropic medications had significantly higher levels of NPY. NPY levels were significantly lower in plasma and cerebrospinal fluid (CSF) in PTSD patients versus controls. Patients with MDD had significantly lower levels of NPY in plasma compared to controls, but not in the CSF. The magnitudes of the decrease in plasma NPY levels were not significantly different between PTSD and MDD. However, chronic stress patients had significantly higher plasma NPY levels compared to controls, PTSD or MDD. Our findings may imply a shared role of NPY in trauma and depression: nevertheless, it is not clear that the association is specific to these disorders. Psychotropic medications may help restore NPY levels. Further controlled studies are needed to better delineate the contribution of confounding variables such as type of depression, body mass index, appetite or sleep architecture. Abstract : We did a rigorous meta‐analysis to clarify discrepancies in the literature concerning the plasma and cerebrospinal fluid levels of neuropeptide Y (NPY) in subjects with major depressive disorder (MDD), post‐traumatic stress disorder (PTSD), and chronic stress. The overall effect size of the 35 pooled studies indicates that NPY levels are lower in patients with PTSD and MDD, compared to healthy controls (but not in chronic stress). Moreover, we found strong evidence of that the use of psychotropic medications and female gender are associated with higher levels of NPY.